2020
DOI: 10.1038/s41598-020-63876-x
|View full text |Cite
|
Sign up to set email alerts
|

Body perception in chimpanzees and humans: The expert effect

Abstract: Both humans and chimpanzees have better performances when recognizing faces or bodies when the stimuli are upright compared to inverted. This is called the inversion effect. It suggests that these two species use a specific way to process faces and bodies. Previous research has suggested that humans also show the inversion effect to objects that they have expertise about, and this is called the expert effect. We investigated whether chimpanzees show the expert effect and how humans and chimpanzees differ by te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
0
13
3
Order By: Relevance
“…Chimpanzee participants showed the inversion effect to chimpanzee bodies, regardless of body posture. As human experts, our chimpanzee participants did not show the inversion effect to bipedal humans with unfamiliar postures in a previous study (Gao et al, 2020), but they showed the inversion effect to bipedal humans with familiar postures, as well as crawling humans, in this study. The inversion effect was also found in the horse and monkey conditions although the chimpanzees had never seen horses.…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…Chimpanzee participants showed the inversion effect to chimpanzee bodies, regardless of body posture. As human experts, our chimpanzee participants did not show the inversion effect to bipedal humans with unfamiliar postures in a previous study (Gao et al, 2020), but they showed the inversion effect to bipedal humans with familiar postures, as well as crawling humans, in this study. The inversion effect was also found in the horse and monkey conditions although the chimpanzees had never seen horses.…”
Section: Discussioncontrasting
confidence: 70%
“…The chimpanzees showed the inversion effect to both chimpanzee body conditions (quadrupedal and bipedal), regardless of their postures. They also showed the inversion effect to crawling humans and bipedal humans with familiar postures in this study, while they did not show this response to bipedal humans with unfamiliar postures in the previous study (Gao et al, 2020). These results suggest that, for conspecifics, the postures do not matter, whether they are Chimpanzees used both visual and embodied cues when processing human bodies.…”
Section: Single-condition Analysescontrasting
confidence: 51%
See 3 more Smart Citations